International differences in chronic kidney disease prevalence: a key public health and epidemiologic research issue. (16th February 2017) - Stel, Vianda S.; Brück, Katharina; Fraser, Simon; Zoccali, Carmine; Massy, Ziad A.; Jager, Kitty J.
Abstract: In this narrative review, we studied the association of risk factors for chronic kidney disease (CKD) and CKD prevalence at an ecological level and describe potential reasons for international differences in estimated CKD prevalence across European countries. We found substantial variation in risk factors for CKD such as in the prevalence of diabetes mellitus, obesity, raised blood pressure, physical inactivity, current smoking and salt intake per day. In general, the countries with a higher CKD prevalence also had a higher average score on CKD risk factors, and vice versa. There was no association between cardiovascular mortality rates and CKD prevalence. In countries with a high CKD prevalence, the prevention of noncommunicable diseases may be considered important, and, therefore, all five national response systems (e.g. an operational national policy, strategy or action plan to reduce physical inactivity and/or promote physical activity) have been implemented. Furthermore, both the heterogeneity in study methods to assess CKD prevalence as well as the international differences in the implementation of lifestyle measures will contribute to the observed variation in CKD prevalence. A robust public health approach to reduce risk factors in order to prevent CKD and reduce CKD progression risk is needed and will have co-benefits for other noncommunicable diseases.